UJI KEMAMPUAN CUKA KAYU MERANTI SEBAGAI BAHAN PENGGUMPAL LATEKS ALAMI - Gatot Subandono; Siti Hamidah; Trisnu Satriadi (Jurnal Sylva Scienteae, 2020)
This study aims to determine the effect of meranti wood vinegar on the speed of clumping latex, as well as knowing the type of meranti wood vinegar and the most optimal concentration as latex clumping material and knowing the color and smell of latex clumping using 3 (three) meranti wood vinegar in Various benefits. The expected benefits of the research are obtaining natural latex coagulation which can be used as a substitute for coagulants which have been used by rubber farmers so that it can produce clumping speed and better quality of latex that does not pollute the environment. month, from December 2018 to March 2019. The results of the study showed that the latex which was given a clumping material in the form of meranti wood vinegar, agglomerates faster than natural latex which is clumped (without clotting material). Latex given clumping material from wood vinegar only takes 12 to 56 minutes to clot, while if allowed to clump naturally it takes up to 480 minutes. The provision of yellow meranti (Shorea multiflora) wood vinegar with a concentration of 20% produces the fastest time for the latex clumping process, the fresh latex does not smell foul but the resulting latex has black spots. Latex which is given a clumping material in the form of meranti wood vinegar does not cause a foul odor, while the one that clumps naturally stinks. However, giving meranti wood vinegar at certain concentrations can cause black spots, especially if using red meranti (Shorea pinanga)  vinegar. If you want odorless and colorless latex, the coagulation material should be selected from 15% white meranti  ((Shorea bracteolatadyer) wood vinegar. From the results of this study it is recommended that meranti wood vinegar (especially yellow meranti wood and white meranti vinegar) can be recommended as an alternative natural coagulation material that can be used by rubber farmers. Meranti leather waste can be collected and used to make wood vinegar, which can later be made into a useful product for  clumping latex.Keywords: wood vinegar; Shorea bracteolatadyer; Shorea pinanga; Shorea multiflora; latex; coagulation